2023
DOI: 10.3389/fmech.2023.1130407
|View full text |Cite
|
Sign up to set email alerts
|

Influence of active cooling on microstructure and mechanical properties of wire arc additively manufactured mild steel

Abstract: Additive manufacturing (AM) of metals attracts attention because it can produce complex structures in a single step without part-specific tooling. Wire arc additive manufacturing (WAAM), a welding-based method that deposits metal layer by layer, is gaining popularity due to its low cost of operation, feasibility for large-scale part fabrication, and ease of operation. This article presents the fabrication of cylindricalshaped mild steel (ER70S-6) samples with a gas metal arc (MIG)—based hybrid WAAM system. A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
2
2
0
1
Order By: Relevance
“…Rodrigues et al (2022) also reported that the formation of fine-grained structures in the top layer is mainly attributed to the fast cooling rate. Similar microstructural evolution was also attained in the scientific studies of Ahsan et al (2020), Dash et al (2023) and Rodrigues et al (2021) during WAAM of low-carbon steel parts. The elemental composition observed at different sections (Figure 19) is almost aligns with the wire electrode composition (ER70S-6).…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Rodrigues et al (2022) also reported that the formation of fine-grained structures in the top layer is mainly attributed to the fast cooling rate. Similar microstructural evolution was also attained in the scientific studies of Ahsan et al (2020), Dash et al (2023) and Rodrigues et al (2021) during WAAM of low-carbon steel parts. The elemental composition observed at different sections (Figure 19) is almost aligns with the wire electrode composition (ER70S-6).…”
Section: Resultssupporting
confidence: 78%
“…Wire, single bead and multi-layered structure exhibits ferrite diffraction planes, namely, {110}, {200}, {211} and {220}. These reported results are matched with the WAAMed deposits of low-carbon steel (Dash et al , 2023; Nemani et al , 2020; Pattanayak et al , 2022; Raut and Taiwade, 2022). Only in the initial wire sample additional copper diffraction planes are identified ({111} and {200} at 50.3° and 59.2°).…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Запроваджені сучасні методи вирішення проблем адитивного виробництва з використанням технології електродугового зварювання [1][2][3][4] вказують на те, що проведення автоматизованого друку потребує подальшого вдосконалення. Для покращення якості процесу виробництва використовуються сучасні методи контролю за температурою [5][6][7], проте й вони не є автоматизованими. Однією з проблем під час адитивного виробництва є перекриття валиків [8][9], параметри якого залежать так само й від розповсюдження тепла між ними [10][11][12].…”
unclassified